Behind the label : inequality in the Los Angeles apparel industry - Bonacich, Edna (University of California Press, 2000)
In this study, Edna Bonacich and Richard Appelbaum investigate the return of sweatshops to the apparel industry, especially in Los Angeles. The "new" sweatshops, they say, need to be understood in terms of the decline in the American welfare state and its strong unions and the rise in global and flexible production.